Case report: Treatment of psychiatric symptoms for an acromegalic patient with pituitary adenoma - Shi, Zhongyong; Cong, Enzhao; Wu, Yan; Mei, Xinchun; Wang, Yun; Peng, Daihui (Frontiers in Psychiatry, 2022)
Acromegalic patients always demonstrate a wide range of clinic manifestations, including typical physical changes such as acral and facial features, as well as untypical neuropsychiatric and psychological disturbances. However, there is still a lack of clinical guidance on the treatment for acromegalic patients with psychiatric comorbidities. We therefore share this case to provide a reference for clinicians to manage the acromegalic patients with psychiatric symptoms. This case report describes a 41-year-old male with an 8-year history of acromegaly due to growth hormone-secreting pituitary adenoma, the maximum cross-sectional area of which was 42mmx37mm demonstrated by pituitary magnetic resonance imaging (MRI). The patient received conservative medicine treatment by regularly injecting with Sandostatin LAR 10mg per month. Two days before admission, he suddenly presented with an acute psychotic episode. In addition to the typical acromegaly-associated changes, his main clinical presentations were olfactory/auditory hallucinations, reference/persecutory delusions, instable emotion and impulsive behavior. Considering the schizophrenic-like psychoses and course features, he was diagnosed with Brief Psychotic Disorder according to Diagnostic and Statistical Manual of Mental Disorders (DSM-5) after a multidisciplinary consultation and evaluation. He was prescribed Aripiprazole, which had less extrapyramidal symptoms and minimal influence on prolactin elevation, with the dose of 5mg per day to control the psychiatric symptoms and he responded quite well. At the time of discharge and the follow-up two month later, the patient was stable without recurrence of any psychotic symptoms. The levels of growth hormone (GH) and insulin-like growth factor 1 (IGF-1) one week after discharge were 2.22ng/mL [normal range (0-2.47ng/mL)] and 381ug/L [normal range (94-284 ug/L)], respectively, which were similar to those before the psychotic episode. Results from this report further supported that small dose of Aripiprazole had little influence on hormonal levels and the development of pituitary macroadenoma. This particular case emphasizes the importance for the clinician to master and carefully identify the possible symptoms of mental disorders associated with acromegaly, and also highlights the need for further investigation in more efficient treatment strategies for acromegalic cases with psychiatric comorbidities.